Iron‐loaded PLLA nanoparticles as highly efficient intracellular markers for visualization of mesenchymal stromal cells by MRI. (March 2014) - Vernikouskaya, I.; Fekete, N.; Bannwarth, M.; Erle, A.; Rojewski, M.; Landfester, K.; Schmidtke‐Schrezenmeier, G.; Schrezenmeier, H.; Rasche, V.
<x xml:space="preserve">Abstract</x> Monitoring of the fate of cells after injection appears paramount for the further development of cell therapies. In this context magnetic resonance imaging (MRI) is increasing in relevance owing to its unique tissue visualization properties. For assessment of cell trafficking and homing, the cells have to be labeled to become MR visible. The rather low sensitivity of MRI demands dedicated intracellular markers with high payloads of MR contrast agents for ensuring sensitive detection of local cell aggregations. In the presented work the application of custom‐designed nanometer‐sized iron oxide loaded poly‐(l‐lactide) (iPLLA) nanoparticles was investigated. The particles were synthesized by the mini‐emulsion process and evaluated for labeling of mesenchymal stromal cells (MSCs). The efficient cellular uptake and long intracellular retention times of the particles as well as their nontoxicity are demonstrated. The average cellular iron content was 55 pg iron per cell. Further incorporation of, for example, fluorescent dye enables the generation of multireporter particles, providing the great potential for multimodal imaging. The efficiency of these nanoparticles as MRI contrast agent was evaluated in vitro using relaxation rate mapping, yielding relaxivities r2 = 273.3, r2* = 545.1 mm−1 s−1 at 3 T and r2 = 415.7, r2* = 872.3 mm−1 s−1 at 11.7 T. The high r2* relaxivity of the iPLLA nanoparticles enabled visualization of a single labeled cell in vitro at 50‐µm spatial resolution. In vivo evaluation in a rat injury model revealed the potential of the iPLLA particles to efficiently label MSCs for MRI monitoring of ~20 000–40 000 injected cells at 11.7 T. In conclusion the presented work demonstrates the applicability of iPLLA particles as efficient intracellular marker for MSC labeling for monitoring the fate of the cells by MRI. Copyright © 2014 John Wiley & Sons, Ltd.